2016
DOI: 10.1111/cdev.12583
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Child Interaction: Links Between Mother and Child Frontal Electroencephalograph Asymmetry and Negative Behavior

Abstract: It is well accepted that parent-child interactions are bidirectional by nature, yet not much is known about the psychophysiological activity underlying these interactions. We examined, during a parent-child interaction, how a child’s negativity statistically predicted maternal frontal EEG asymmetry and how a mother’s negativity statistically predicted child frontal EEG asymmetry. Thirty-four mother-child dyads participated in the study. Maternal and child behavior and physiology were measured during a puzzle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 85 publications
1
41
0
Order By: Relevance
“…We did not assess whether trauma was resolved or unresolved, and given that unresolved trauma is the risk factor for DMB for which there currently is the most evidence. Future research could examine whether mother and infant negative affectivity contribute to maternal withdrawal, considering that both contribute to the quality of the dyadic interaction (Atzaba-Poria, Deater-Deckard, & Bell, 2017;Wang, Deater-Deckard, & Bell, 2016). Further limitations of the study are that maternal histories of abuse were assessed with only the AAI, using a categorical present/absent classification.…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess whether trauma was resolved or unresolved, and given that unresolved trauma is the risk factor for DMB for which there currently is the most evidence. Future research could examine whether mother and infant negative affectivity contribute to maternal withdrawal, considering that both contribute to the quality of the dyadic interaction (Atzaba-Poria, Deater-Deckard, & Bell, 2017;Wang, Deater-Deckard, & Bell, 2016). Further limitations of the study are that maternal histories of abuse were assessed with only the AAI, using a categorical present/absent classification.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previously used measures (e.g., Atzaba‐Poria et al, 2017), for each mother–child interaction, a mother's general negativity was the number of talk turns in which she expressed negative emotion divided by the overall number of talk turns she had during that interaction.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of affect and physiological changes, research has shown that the influence of infants and parents on one another is bidirectional ( 29 , 30 ). Accordingly, we predicted that ( i ) significant neural coupling would exist between adults and infants during social interaction, ( ii ) direct (and direct-oblique) gaze would both be associated with higher interpersonal neural connectivity than indirect gaze, and ( iii ) in experiment 1 (video), only unidirectional [adult-to-infant (A → I)] coupling would be observed, but in experiment 2 (live), bidirectional [adult-to-infant (A → I) and infant-to-adult (I → A)] coupling would be observed.…”
Section: Predictionsmentioning
confidence: 99%